The Influence of Social Media and Interpersonal Communication on the Voting Behavior of Millennials and Generation Z in the 2024 Presidential Election in Indonesia - Indryani, Ni Luh Putu Caosa; Rahmatunnisa, Mudiyati; Bajari, Atwar; Djuyandi, Yusa (Journal of Cultural Analysis and Social Change, 2025)
The 2024 Indonesian presidential election was dominated by young voters, with Millennials and Generation Z comprising more than half of the electorate and thus becoming decisive actors in electoral democracy. This study examines the influence of social media and interpersonal communication on their voting behavior using a mixed-methods explanatory sequential design that combined a national survey of 1,200 respondents with Focus Group Discussions (FGDs) across seven provinces. Regression analysis confirms that social media—particularly WhatsApp, YouTube, TikTok, and Instagram—significantly shapes political preferences, with Generation Z more influenced by digital narratives while Millennials tend to validate information through face-to-face discussions. Qualitative findings highlight that interpersonal communication remains essential for clarification and reinforcement of political decisions. The integration of both channels creates a complementary ecosystem in which social media provides broad reach, while interpersonal exchanges strengthen legitimacy. The study concludes that effective political communication strategies must combine the immediacy of digital media with the depth of participatory interpersonal engagement.